Use of multiseasonal oil palm yield data to assess drought tolerance - Hermanto, Alex; Siew, Hua Gan; Mustopa, Ivan Rendi; Wei, Chee Wong; Hong, Patrick Chuan Ng; Ngai, Paing Tan; Chun, Wie Chong (Elsevier BV, 2022)
The understanding of yield responses of different oil palm progenies to rainfall is important for plantation management to ensure that the most suitable progeny is selected for maximum productivity. Drought responses are commonly studied using drought induction on oil palm seedlings or by conducting irrigation trials. Nevertheless, such trials may not reflect the yield response in mature palms in natural conditions. In this study, an alternative approach is developed to evaluate oil palm yield responses to varying rainfall regimes. Using the time-series rainfall and yield data of oil palm materials (n = 11), the yield components most affected by rainfall fluctuations were identified. Subsequently, the floral developmental stages susceptible to rainfall changes were determined. Finally, the relative yield performance of the materials in different rainfall conditions was compared to determine the materials adapted to the low rainfall condition. The bunch number was the best parameter to investigate the effect of rainfall on oil palm yield. The floral developmental stages affected by rainfall were inflorescence abortion and sex determination. Progeny-specific yield response is discernible from yield and rainfall data alone. Our study has contributed to the development of an approach to screening for droughttolerant materials.